2017
DOI: 10.1080/2162402x.2017.1339853
|View full text |Cite
|
Sign up to set email alerts
|

The anti-SLAMF7 antibody elotuzumab mediates NK cell activation through both CD16-dependent and –independent mechanisms

Abstract: Elotuzumab is a humanized therapeutic monoclonal antibody directed to the surface glycoprotein SLAMF7 (CS1, CRACC, CD319), which is highly expressed on multiple myeloma (MM) tumor cells. Improved clinical outcomes have been observed following treatment of MM patients with elotuzumab in combination with lenalidomide or bortezomib. Previous work showed that elotuzumab stimulates NK cell-mediated antibody-dependent cellular cytotoxicity (ADCC), via Fc-domain engagement with FcγRIIIa (CD16). SLAMF7 is also express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 49 publications
4
75
0
Order By: Relevance
“…HuLuc63 was also shown to induce similar lysis of patient myeloma cells by NK cells from allogeneic healthy donors as compared to NK cells from the same MM patient, even in patients who were resistant to conventional therapy ( 18 ). Furthermore, HuLuc63 was significantly more effective in inducing ADCC responses by NK cells than another chimerized SLAMF7 antibody (human IgG1-human Fc/mouse variable regions) named ChLuc90 ( 18 , 19 , 39 ). Tai et al also demonstrated that HuLuc63 stimulated ADCC responses by NK cells from healthy donors to a variety of myeloma cell lines, and they further showed strong ADCC of autologous myeloma cells by NK cells from MM patients, even if patients were resistant to conventional therapies ( 19 ).…”
Section: Elotuzumab As a New Therapeutic To Target Multiple Myelomamentioning
confidence: 99%
“…HuLuc63 was also shown to induce similar lysis of patient myeloma cells by NK cells from allogeneic healthy donors as compared to NK cells from the same MM patient, even in patients who were resistant to conventional therapy ( 18 ). Furthermore, HuLuc63 was significantly more effective in inducing ADCC responses by NK cells than another chimerized SLAMF7 antibody (human IgG1-human Fc/mouse variable regions) named ChLuc90 ( 18 , 19 , 39 ). Tai et al also demonstrated that HuLuc63 stimulated ADCC responses by NK cells from healthy donors to a variety of myeloma cell lines, and they further showed strong ADCC of autologous myeloma cells by NK cells from MM patients, even if patients were resistant to conventional therapies ( 19 ).…”
Section: Elotuzumab As a New Therapeutic To Target Multiple Myelomamentioning
confidence: 99%
“…Since SLAMF7 is also expressed on NK cells, the cross-linking of SLAMF7 on NK cells by a treatment with elotuzumab induces NK cell activation via immunoreceptor tyrosine-based switch motifs (ITSM)-mediated signaling. These ITSM-mediated signaling enhances calcium signaling from ITAM-linked activating receptor, through an interaction between NKp46 and NKG2D and their ligands expressed on myeloma cells [142] or stimulates macrophage-mediated ADCP [143]. The phase III ELOQUENT-2 study (elotuzumab plus lenalidomide and dexamethasone vs lenalidomide and dexamethasone) reported a 29% reduction in risk of death or disease progression at 4 years in the elotuzumab arm of the trial [144] (Table S1).…”
Section: Inkt and Nk Cell-mediated Immunotherapymentioning
confidence: 99%
“…Elotuzumab is a humanized IgG-1 monoclonal antibody targeting SLAMF7 that promotes NK-mediated ADCC, directly activates NK cells and interferes with the MM cell adhesion to the bone marrow stromal cells [63][64][65]. Elotuzumab showed no clinically meaningful activity when administered as a single agent-in a phase I dose-escalating study, the best response achieved by RRMM patients treated at different doses of elotuzumab was stable disease (SD, 26%) [66] (Table 3).…”
Section: Clinical Developmentmentioning
confidence: 99%